(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Aims: This research work was about biorelevant dissolution method development for fluvoxamine extended-release capsule by correlating preprandial and postprandial in vivo performance. Materials and Methods: The mean plasma concentration profile obtained after oral administration of extended-release capsules was deconvoluted using Wagner-Nelson deconvolution technique, to achieve percentage fraction of drug absorbed, and target dissolution profile was derived. Biorelevant dissolution method was developed using USP Apparatus-3, with dissolution media simulating gastrointestinal tract sink condition. A full factorial design of experiment was carried out for optimizing dissolution volume and dips per minutes, to achieve target dissolution profile. Results: The dissolution results observed using office of generic drugs recommend dissolution method were not comparable with target dissolution profile and observed with F2 value of 37 at preprandial and 43 at postprandial condition. The achieved dissolution profile was comparable with target and observed with F2 value of 81 at preprandial condition and 85 at postprandial condition. Conclusion: The developed dissolution method establishes good correlation between in vitro drug release and in vivo drug absorption and observed with R2 value of 0.998 at preprandial condition and 0.997 at postprandial condition. The method gives the advantage of giving biowaiver.